VOLUMETRIC PRODUCTION OF EUCALYPTUS SPP. CLONES UNDER DIFFERENT SPACING IN A SEVERE DROUGHT PERIOD IN THE SEMI-ARID REGION OF PERNAMBUCO, BRAZIL - Silva, José Wesley Lima; Silva, José Antônio Aleixo da; Tavares, José Alves (Floresta, 2022)
<p id="docs-internal-guid-2badcb6f-7fff-9ad9-30c3-cbb375f77786" style="line-height: 1.2; margin-left: 28.34645669291339pt; margin-right: 28.34645669291339pt; text-align: justify; margin-top: 0pt; margin-bottom: 0pt;" dir="ltr">The adaptation of Eucalyptus clones in the Chapada of Araripe, PE, Brazil was observed after implementing experiments with fast-growing forests. This region has a high demand for alternative energy sources due to the Gypsum Pole, basically maintaining its energy matrix from the exploitation of Caatinga vegetation. Therefore, as a way to increase the gains in volumetric productivity in planting Eucalyptus spp. clones, it is important to understand which spacing levels provide the best competition between individuals. Thus, the objective of this study was to evaluate if the volumetric productivity of Eucalyptus spp. clones is affected by different spacing levels in stands implanted under severe weather conditions in Chapada of Araripe, PE, Brazil. The experiment was carried out at the Experimental Station of the Pernambuco Agronomic Institute (IPA) in the municipality of Araripina, PE, Brazil. Three Eucalyptus clones (C11, C39 and C41) with five spacing levels (2 m x 1 m, 2 m x 2 m, 3 m x 2 m, 3 m x 3 m and 4 m x 2 m) were arranged in a completely randomized design with factorial arrangement (3 x 5). The survival rate of the experiment was higher than 94%, even under conditions of water stress. The highest volume productivity was obtained with the C39 clone in the 2 m x 1 m spatial arrangement. The spatial arrangement strongly influences productivity. Even with the severe drought condition regulating productivity, the C39 clone showed MAI values of 15.92 m3 ha-1 year-1.